NEW AND CRITICAL MALAYSIAN PLANTS VI - A. J. G. H. KOSTERMANS (BRIN Publishing (Penerbit BRIN), 1960)
1. Alseodaphne Nees and Nothaphoebe Bl. are reinstated as distinct genera. 2. Newly described are Alseodaphne corneri Kosterm., A. montama Kosterm.; Nothaphoebe paehyphylla Kosterm. and N. pahangensis Kosterm. 3. Iteadaphne philippinensis Elmer is relegated to Alseodaphne. 4. Newly described in Beilschmiedia are: B. filicifolia Kosterm., B. glaueiphylla Kosterm., B. pilosa Kosterm. 5. Endiandra eusideroxylocarpa Kosterm., a new species from Borneo. 6. Dehaasia hirsute/, Kosterm., a new species from Borneo. 7. A new Millettia (M. vasta Kosterm.) is described from Borneo with notes on its distributional area. 8. Lansivm dornesticum, var. aquewm Jack (a common market fruit in Sumatra, Java and S. Borneo) is raised to specific rank. 9. Teijsmanniodendron pendulum Kosterm., a new species from Central-East Borneo.